Unpleasant Life Occurrences as determinants of mental health status among (2018)
Psychological disturbance among the general populace has been linked to behaviours which damage physical health and cause mental problems in later adulthood. Most mental health problems diagnosed in adulthood begins in adolescence. The purpose of the study was to explore the determination of unpleasant life occurrences on mental health status among undergraduates of the University of Ibadan. The study was a survey research design which employed purposive. stratified and simple random sampling technique to select (1,047) respondents from (1 departments out of (12) faculties to get the sample size. The instruments for the study were adapted and self-developed questionnaire with a reliability of0.700. Two hypotheses were tested and data collected and analyzed using frequency counts, percentages and inferential statistics of t- test. A NO VA, PPMC and regression models al 0.05 alpha level. The results show that undergraduates in the University of Ibadan have poor mental health status. It is also concluded that female undergraduates recorded lower mental health status than their male counterparts. The paper recommends that the University should promote a climate of awareness and support for student’s mental health, wellness and stress reduction. It also recommends the University should offer, and in some cases require training on mental health awareness and resources for faculty staff and students as well as involvement in Physical exercises by the students. This will reduce the stress in the body and improve the mental health